#cyprus #coffee: Trends in the Linguistic Communication of Young Greek-Cypriots as Reflected in Coffee Promotion on Instagram. - Papadima, Aspasia (My University, 2023)
yprus is currently undergoing significant transformations that underscore its rich multicultural diversity and impact various aspects, including language and its development. As language communication adapts to balance cultural specificity with extroversion, global trends, and emerging forms of linguistic expression, Cyprus' linguistic landscape exhibits distinctiveness due to the prominence of two linguistic varieties: Cypriot-Greek (CG), the language variety of Greek-Cypriots, and Standard Modern Greek (SMG), the official state language. While SMG serves formal contexts, CG thrives in everyday oral communication, folk literature, and humor. Nevertheless, in recent years, CG has increasingly permeated previously considered inappropriate contexts, such as public speeches, broadcasted discussions, political debates, and advertising, in both spoken and written communication. Simultaneously, the growing influence of English as a means of communication among young Greek-Cypriots reflects contemporary global linguistic trends while echoing Cyprus' colonial history. The coffee tradition holds immense cultural significance in Cypriot society, demanding considerable time for preparation and consumption. However, contemporary lifestyles, socio-economic conditions, and global influences necessitate innovative approaches to coffee products and their promotion. Targeting younger audiences, budget-friendly canned coffee has garnered substantial popularity among young Greek-Cypriots, particularly through social media platforms like Instagram. This study focuses on Mr. Brown’s canned coffee as a case study for coffee advertising promotion on Instagram. It draws upon sociolinguistics and advertising theories, employing semiotic analysis as an interpretive tool. The study's objectives encompass documenting, analyzing, and discussing the use of CG in brand promotion, identifying current linguistic trends and codes in multimodal advertising messages targeting Greek-Cypriot youth, highlighting the cultural significance of specific representational and language choices, and exploring the impact of globalization on local culture and language. The sociolinguistic context of Cyprus, influenced by both cultural and historical factors, presents a unique dynamic in which CG and SMG play distinct roles based on ideology, function, and prestige. This research uncovers how Mr. Brown's canned coffee strategically integrates CG into its Instagram promotion to target young Greek-Cypriots. The brand's Instagram content emphasizes local customs, traditions, and natural beauty, resonating primarily with young Greek-Cypriot men. Semiotic analysis reveals how Mr. Brown's visual identity, with its character design and typographic choices, reinforces gendered characteristics while enhancing the brand's prestige. The study also identifies gendered language in the promotion that perpetuates heteronormativity, reinforcing traditional roles and cultural norms. Many posts adopt a user-generated content model, allowing users to engage personally with the brand. The posts further integrate the brand's character/logo, blurring the line between influencer and product. The research in Mr. Brown’s Instagram captions also reveals extensive use of CG, emojis, emphasis through semiotic features, pragmatic punctuation, and code-switching between CG and English. English hashtags enhance outreach, while Cyprenglish reflects Cypriot identity, glocality and humor. In conclusion, Mr. Brown's canned coffee promotion in Cyprus strategically incorporates CG, cultural specificity, and historical roots to connect with young Greek-Cypriots. By embracing the cultural identity and aspirations of its target audience, the brand fosters pride, familiarity, and cultural preservation. This study offers valuable insights into the intersection of language, culture, and advertising in contemporary Cyprus.
Keywords: Cypriot-Greek; Instagram promotion; Cultural identity; Gendered language; Glocality